Event Reservation System (EVERS) / Rabiatul Adawiya Razali - Razali, Rabiatul Adawiya (2016)
Usually customers make reservation through direct hotline to have a quick deal with the owner of the place they want to reserve. Hotel UiTM Dungun Terengganu current process is using direct hotline to entertain their customers quickly but do not have a proper way in keeping the reservation data. Computerized reservation system is the online reservation system that will be implementing in the Hotel UiTM Dungun based on the case study with the sales and marketing staff to collect some information have been done. Event Reservation System (EveRS) is the online reservation system that has been developed to improve the sales and marketing department current business process. In developing EveRS, System Development Life Cycle (SDLC) was being used as a method to guide the whole process of the EveRS development. The model used for EveRS is Prototype Model which has two version of improvement when having consultation with the sales and marketing staff. This is to make sure the development of EveRS develop continuously according to the plan and the users will get better understanding. Besides that, system testing plan and evaluation from user and experts also was prepared as a method to improve the functionality, usability and design interface of the system. The respondents experienced that EveRS is useful to the users by received mean for perceived usefulness is 4.23. One of the recommendations for future enhancement is developed computerized system can be used in smartphone.